Ethnomathematics-Based Edutainment: Exploring the Enhancement of Mathematical Reasoning Skills Through Video Games - Novitasari, Dwi; Kertiyani, Ni Made Intan; Wulandari, Nourma Pramestie (Insitut Agama Islam Negeri Kerinci, 2024)
This study aims to develop an ethnomathematics-based visual novel game, named